Phenomenological variables of autobiographical memory narratives associated with healthy habits in children - Aguilar-Córcoles, Maria José; Navarro-Bravo, Beatriz; Esparcia-Moreno, Mercedes; Latorre-Postigo, José Miguel; Ricarte-Trives, Jorge Javier (Anales de Psicología / Annals of Psychology, 2023)
Different studies relate self-defining memories (SDM) to psychological well-being and health. This study aims to analyze the relation between the phenomenological variables (e.g., emotional intensity, vividness etc.) involved in self-defining memories associated with health (HSDMs) and healthy habits in 262 children aged between 9 and 13 years. Participants’ eating habits and physical activity events are associated with the emotionality of their HSDMs. Most of the HSDMs were declared to be experienced with their family members, and greater importance was attributed to those memories related to mothers. Significant features of retrieved HSDM can be detected from construction of autobiographical memories supporting the development of a robust healthy self in children. As such, families and schools should facilitate life experiences that lead to the formation of vivid and detailed HSDMs given that this is likely to promote health-related behaviours.